Code Switching in Di Balik Pintu Vlog By Boy William - Hestin Nurvadhilah; Adip Arifin; Ratri Harida (English Language Education Department, Universitas Majalengka, 2022)
This research aims to identify the different kinds of code switching, the factors that cause code switching, and the function of code switching as it was employed in Boy William's Di Balik Pintu vlog. The researchers used descriptive qualititave research. The findings of this study demonstrated the use of tag switching, intersentential switching, and intrasentential switching as the three types of code switching in Di Balik Pintu vlog by Boy William. The researchers found 129 data, 24 intersentential switching data, 74 intrasentential switching data, and 31 tag switching data. The results of the factors that cause code switching were 75 data, there are 34 data of speakers, 28 data of interlocutors, 7 data of situation change from formal to informal, 5 data of change discussion topic, 1 data of attendance of the third person. While for the function of code switching, there were 129 data. The researchers found 19 quotation, 12 addressee specification, 25 interjections, 14 reiterations, 22 message qualification, and 37 personalization or objectification. This research can be used to increase knowledge about code switching and as reference for the next researcher.